1999
DOI: 10.1007/s007750050382
|View full text |Cite
|
Sign up to set email alerts
|

Double-strand DNA hydrolysis by dilanthanide complexes

Abstract: Although there has been progress in developing artificial hydrolytic DNA cleaving agents, none of these has been shown to carry out the double-strand hydrolysis of DNA. We demonstrate that La(III) or Ce(IV) combined with the ligand 1,3-diamino-2-hydroxypropane-N,N,N', N'-tetraacetate (HPTA) in a 2 : 1 ratio can efficiently cleave supercoiled plasmid DNA at 55 degrees C within a 3-h period. Analysis of end-labeled restriction fragments cleaved by these complexes reveals 3'- and 5'-ends consistent with a hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 0 publications
2
29
0
Order By: Relevance
“…To confirm this conclusion we then analyzed our results using the model developed Cowan and co-workers [55] that specifically addresses situations where there are mixed single-strand breaks and double-strand cuts. The n 1 /n 2 values applying Cowan's method (Table 7) show the participation of a double-strand cleavage path for efficient linear DNA production [23,81,82]. Interestingly, the k obs1 and t 1/2 values for our compounds are comparable to those of other Cu(II) compounds that exhibited nonrandom double-strand DNA cleavage [74].…”
Section: Kinetic Study Of Dna Cleavage By Complexes 2 Andsupporting
confidence: 70%
“…To confirm this conclusion we then analyzed our results using the model developed Cowan and co-workers [55] that specifically addresses situations where there are mixed single-strand breaks and double-strand cuts. The n 1 /n 2 values applying Cowan's method (Table 7) show the participation of a double-strand cleavage path for efficient linear DNA production [23,81,82]. Interestingly, the k obs1 and t 1/2 values for our compounds are comparable to those of other Cu(II) compounds that exhibited nonrandom double-strand DNA cleavage [74].…”
Section: Kinetic Study Of Dna Cleavage By Complexes 2 Andsupporting
confidence: 70%
“…A dinuclear tetravalent cerium complex Ce 2 (HXTA) (HXTA: 5-methyl-2-hydroxyl-1,3-xylene-␣,␣-diamine-N,N,N ,N -tetraacetic acid) has been shown to effect double-stranded cleavage by a hydrolytic pathway to yield linear plasmid DNA [78]. Although the yields of linear products were low (∼20%), the catalysts were functional with high regioselectivity at 37 • C and pH 8, and gave 5 -OPO 3 -and 3 -OH-labeled end products in high yield (>90%), like the products of natural DNA hydrolyzing enzymes; a clear improvement over earlier complexes Ce 2 (HPTA) and La 2 (HPTA) (HPTA: 2-hydroxylpropenylene-1,3-diamine-N,N,N ,N -tetraacetic acid) [79]. These two dinuclear complexes worked effectively at higher temperatures, i.e.…”
Section: Dinuclear Rare-earth Complexesmentioning
confidence: 98%
“…Recently, Branum and Que [69] have reported that the La(III) or Ce(IV) complexes of 1,3-diamino-2-hydroxypropane-N,N,N9, N9-tetraacetate (HPTA) in a 2:1 ratio can efficiently cleave supercoiled DNA at 55 C within 3 h. Although no mechanistic details are provided, nor the kinetics of hydrolysis evaluated, these lanthanide complexes demonstrate non-enzymatic double-strand hydrolysis of DNA, one of only a small number of complexes known to show such chemistry [36]. Efficient ªenzyme-likeº double-strand cleavage has been documented for metalloaminoglycosides by an oxidative pathway [36,37].…”
Section: General Conclusionmentioning
confidence: 98%